Knowledge on intravenous therapy among undergraduate nursing students in Pokhara, Nepal: A cross-sectional study - Thapa, Cheena; Shrestha, Nisha; Banstola, Ratna Shila (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Intravenous therapy is a fundamental skill for nurses, and assessing student’s knowledge is crucial for ensuring patient safety. This study was aimed to assess the knowledge on intravenous therapy among undergraduate nursing students in Gandaki province, Pokhara. Methods: A cross-sectional study was conducted among purposively selected 208 undergraduate nursing students in Pokhara. Pretested structured self-administered questionnaire was used to collect data which was validated and reliable (r=0.85). Data was analyzed in SPSS version 22.0, using descriptive and inferential statistics (Chi-square test and logistic regression) p-value <0.05 was considered significant. Results: The study revealed that 63% had adequate, 35.1% had moderate and 1.9% had inadequate level of knowledge with a mean score of 42.43±7.77. Multivariate logistic regression showed those getting information from friends/senior were twice more likely to have adequate knowledge (p=0.01; AOR= 2.37; CI=1.20, 4.70) and students having clinical experience of ≥2 years were 2.5 times more likely to have adequate knowledge (p=0.04; AOR=2.54; CI=0.99, 6.55). Conclusions: The study finds undergraduate nursing students possess sufficient general knowledge of intravenous (IV) therapy, gaps in understanding specific areas like drop factor calculation, recognizing infiltration signs, preventing infection, and the importance of routine IV care, can compromise care quality and patient safety. Furthermore, students should supplement information from peers and seniors with formal education including skills-based training focused on these critical aspects of IV therapy to ensure competency.